Comparison of Outcomes of Hybrid and Surgical Correction for De Novo Arteriovenous Graft Occlusion - Ko, Dai Sik; Choi, Sang Tae; Lee, Won Suk; Chun, Yong Soon; Park, Yeon Ho; Kang, Jin Mo (Vascular Specialist International, 2018)
This study aimed to compare surgical revisions and balloon angioplasty after surgical thrombectomy on thrombosed dialysis access as a first event. Records of patients undergoing creation of arteriovenous grafts (AVGs) at the Gachon University Gil Medical Center between March 2008 and February 2016 were reviewed. Among them, patients who underwent treatment on first-time thrombotic occlusion after AVG creation were identified. Outcomes were primary, primary-assisted, and secondary patency. The patency was generated using the Kaplan-Meier method, and patency rates were compared by log-rank test. A total of 59 interventions (n=26, hybrid interventions; n=33, surgical revisions) for occlusive AVGs were identified. The estimated 1-year primary patency rates were 47% and 30% in the surgery and hybrid groups, respectively. The estimated primary patency rates were not different between the two groups (log-rank test, P=0.73). The Kaplan-Meier estimates of 6 and 12 months for primary-assisted patency rates were 68% and 57% in the surgery group and 56% and 56% in the hybrid group. The Kaplan-Meier estimates of 12 and 24 months secondary patency rates were 90% and 71% in the surgery group and 79% and 62% in the hybrid group. There were no differences in the estimated primary-assisted and secondary patency rates between the two groups. Our results showed no significant difference between the two groups in terms of primary patency (P=0.73), primary-assisted patency (P=0.85), and secondary patency (P=0.78). However, percutaneous transluminal angioplasty can give more therapeutic options for both surgeons and patients.